Renewable energy between limited use and treatment of the electricity crisis in Iraq - DADOOSH, ALI ABDULKADHIM (Journal of Economics and Administrative Sciences, 2020)
The electric energy is one of the most important renewable energies used in the world as it is the main source for sustainable development and economic development through its use in (production, transport and distribution), and in Iraq, the electric power sector has suffered from many problems and obstacles, as providing electric current is one of the most prominent difficulties and challenges That successive governments and residents have faced since the early nineties of the last century and are still ongoing, and that Iraq has all the climatic conditions for developing the work of the electricity system from renewable energies such as solar and hydroelectric energy, as well as gas fields that have become a Basic pillar of power generation operations in the world, especially since - natural gas - is one of the energies of environmentally friendly and cost of the economic and financial terms in the country.